Prevalence of Gymnophalloides seoi infection in coastal villages of Haenam-gun and Yeongam-gun, Republic of Korea - Guk, Sang-Mee (The Korean Society for Parasitology, 2006)
One coastal village in Haenam-gun and two in Yeongam-gun, Jeollanam-do were surveyed for intestinal parasite infections by fecal examination. The egg positive rates of Gymnophalloides seoi were high, 24.1% (14/58) in Haenam-gun and 9.3% (11/118) in Yeongam-gun. The egg positive rates of heterophyids, including Heterophyes nocens, and of Clonorchis sinensis were 10.3% and 6.9% in Haenam-gun, and 14.4% and 8.5% in Yeongam-gun, respectively. After praziquantel treatment and purgation, a total of 37,761 fluke specimens were recovered from 17 patients; 11 in Haenam-gun and 6 in Yeongam-gun. Gymnophalloides seoi was the most commonly recovered species, with 37,489 specimens in total (2,205 per person). Other recovered flukes included Heterophyes nocens, Stictodora fuscata, Heterophyopsis continua, Pygidiopsis summa, and undetermined species. These results indicate that the areas surveyed are new endemic foci of G. seoi.